The impact of climate change on Black Spruce colonisation of snow beds near the tree-line by Boniface River, Nunavik - Lévesque, Esther; Boulanger-Lapointe, Noémie (Polar Data Catalogue, 2015)
Cartography of the landscape major components including microtopography and localisation of trees (Black Spruce) and shrubs, using a theodolite. Characterization of trees height, diameter at breast height and number of cones, and the seedlings height and diameter at breast height. Seed germination and viability tests in laboratory.